2020
DOI: 10.1111/mec.15418
|View full text |Cite
|
Sign up to set email alerts
|

Parentage analyses identify local dispersal events and sibling aggregations in a natural population of Millepora hydrocorals, a free‐spawning marine invertebrate

Abstract: Dispersal is a critical process for the persistence and productivity of marine populations. For many reef species, there is increasing evidence that local demography and self-recruitment have major consequences on their genetic diversity and adaptation to environmental change. Yet empirical data of dispersal patterns in reef-building species remain scarce. Here, we document the first genetic estimates of self-recruitment and dispersal distances in a free-spawning marine invertebrate, the hydrocoral Millepora c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 108 publications
1
27
0
Order By: Relevance
“…The results of the settlement experiments, together with the differential survival of settlers in-situ indicate that biological responses and parental effects may impose selective constraints on larval dispersal, settlement, and survival. These adds to the accumulating evidence of a more specific or local larval retention within reefs 59,[74][75][76][77][78] , suggesting that populations of some marine species may be less "open" 59 than traditionally believed and are structured, to some extent, in a niche-or habitat-dependent manner related to their natal environment. Importantly, although we have investigated two main environmental factors (i.e., light regime and settlement substrate), there might be additional factors that further constrain dispersal and connectivity.…”
Section: Resultsmentioning
confidence: 77%
“…The results of the settlement experiments, together with the differential survival of settlers in-situ indicate that biological responses and parental effects may impose selective constraints on larval dispersal, settlement, and survival. These adds to the accumulating evidence of a more specific or local larval retention within reefs 59,[74][75][76][77][78] , suggesting that populations of some marine species may be less "open" 59 than traditionally believed and are structured, to some extent, in a niche-or habitat-dependent manner related to their natal environment. Importantly, although we have investigated two main environmental factors (i.e., light regime and settlement substrate), there might be additional factors that further constrain dispersal and connectivity.…”
Section: Resultsmentioning
confidence: 77%
“…The perceived chaos in reefbuilding corals is -at least in part-due to a mismatch in spatial resolution (Cros et al, 2020), a predominance of populationlevel sampling (Riginos and Liggins, 2013;Liggins et al, 2019), and an almost complete lack of temporal assessments (but see Williams et al, 2014;Underwood et al, 2018). Microsatellitebased studies with exhaustive local sampling have demonstrated the critical relevance of fine-scale, individual-based sampling by revealing the important contributions of clonality and inbreeding (Gorospe and Karl, 2013;Dubé et al, 2017), sperm dispersal and self-fertilization (Warner et al, 2016), co-dispersal of siblings, and self-recruitment (Cros et al, 2020;Dubé et al, 2020). Nonetheless, our understanding of reproduction and dispersal processes in benthic reef organisms is still in its infancy given that spatially explicit, individual-based attempts have been incredibly tedious, and have lacked the ability to characterize and integrate the fine-scale composition and configuration of the reefscape.…”
Section: Why Reefscape Genomics?mentioning
confidence: 99%
“…Depending on camera resolution and altitude (i.e., distance to seafloor), current modeling abilities roughly span a grain range of ∼0.1-10 mm and spatial extent range of 0.01-1 ha (Figure 2), with a trade-off between grain size and spatial extent. Using scale references, a highly accurate local coordinate system of the generated model can be created (mm to cm accuracy; Ledoux et al, 2010), enabling underwater mapping with unprecedented resolution, efficiency, and repeatability compared to traditional methods using transect tapes, depth gages, and/or compasses (Foster et al, 2013;Gorospe and Karl, 2013;Williams et al, 2014;Gélin et al, 2017;Dubé et al, 2017Dubé et al, , 2020. Such local coordinates can be converted to real-world coordinates by georeferencing the model using, e.g., ground control points (GCPs) or by integrating acoustic positioning and orientation sensors on the imaging platform [e.g., ultrashortbaseline (USBL), Doppler velocity log (DVL), and attitude and heading reference systems (AHRS)].…”
Section: Reefscape Characterization Through Close-range Photogrammetrymentioning
confidence: 99%
“…In the marine environment, evidence of delayed dispersal comes from very few species that do not have a larval dispersal phase, such as the damselfish Acanthochromis polyacanthus (Miller‐Sims et al, 2008), and/or are organized in eusocial societies, such as snapping shrimp of the genus Synalpheus (Duffy, 1996). Support for the kin cohesion hypothesis is found in a number of examples of full and half siblings near each other in marine species (e.g., Bernardi et al, 2012; Buston et al, 2009; Dubé et al, 2020; Herrera et al, 2016; Riquet et al, 2017; Selkoe et al, 2006). Finally, evidence for limited dispersal comes from observations of high levels of self‐recruitment to local populations for a range of species (e.g., Almany et al, 2007; Beldade et al, 2012; D'Aloia et al, 2013; Jones et al, 1999, 2005; Rueger et al, 2020; Saenz‐Agudelo et al, 2012; Selwyn et al, 2016; Swearer et al, 1999) and from dispersal curves showing that the probability of successful dispersal declines as a function of distance (Almany et al, 2013, 2017; Buston et al, 2012; D'Aloia et al, 2015; Williamson et al, 2016).…”
Section: Introductionmentioning
confidence: 97%